Liver kinase B1 overexpression controls mycobacterial infection in macrophages via FOXO1/Wnt5a signaling. Issue 1 (11th September 2018) - Cui, Junwei; Li, Mingying; Liu, Weiguo; Zhang, Bianfang; Sun, Bing; Niu, Wenyi; Wang, Yongliang
Abstract: Mycobacterium tuberculosis (Mtb) is a primary cause of tuberculosis (TB), which has infected more than one‐third of the world's population. Mtb survival and subsequent inflammation in macrophages are important components of TB. Liver kinase B1 (LKB1) has demonstrated anti‐inflammation effects, but its function and underlying mechanism in mycobacteria‐infected macrophages remains unknown. In the current study, we discovered that LKB1 was markedly decreased in Mtb‐infected THP‐1 and U937 macrophages. Moreover, LKB1 overexpression inhibited Mtb survival in macrophages. Mtb infection increased expression of nitric oxide, inducible nitric oxide synthase, and inflammation‐related cytokines interleukin (IL)‐6, tumor necrosis factor‐α, and IL‐1β, whereas pcDNA3‐LKB1 transfection inhibited the release of these cytokines in THP‐1 and U937 cells. Furthermore, LKB1 overexpression significantly decreased protein expression of Wnt5a, which is dependent on the elevation of forkhead box protein O1 (FOXO1). Generally, we show that interruption of FOXO1 or overexpression of Wnt5a can reverse the effects of LKB1 on mycobacterial intracellular survival, nitric oxide, inducible nitric oxide synthase expression, and inflammatory cytokine release. These findings indicate important roles for LKB1, FOXO1, and Wnt5a in controlling mycobacteria and cell inflammation. Abstract : These findings indicate important roles for liver kinase B1, forkhead box protein O1, and Wnt5a in controlling mycobacteria and cell inflammation. IL, interleukin; Mtb, Mycobacterium tuberculosis ; TNF‐ α, tumor necrosis factor‐α.